SOCIAL MEDIA NETWORKING AND COLLABORATING LEARNING AS CORRELATES OF PRINCIPALS’ PERFORMANCE IN PUBLIC SECONDARY SCHOOLS IN DELTA STATE, NIGERIA - Ebunu, A. A.; ONYEIKE, DR. V. C. (Archives of Business Research, 2021)
This study examined the relationship between social media networking, collaborating learning and principals’ performance in public secondary schools in Delta State. Two research questions guided the study. Two hypotheses were also tested in the study at 0.05 significant level. The study adopted the correlation design. The study population was the 427 principals in public secondary schools in Delta State Post-Primary Education Board. The sample size was 342 principals serving in public secondary schools in Delta State. The multistage sampling technique was used to select the sample. The instruments used to generate data were two questionnaires social media networking, collaborating learning and principals’ performance, with reliability coefficients of 0.96 and 0.89 (SMNCL) and (PPQ). The generated data were analyzed using Pearson r and simple regression, t-test associated with simple regression. The findings of the study revealed that social media networking had a positive and strong relationship with principals’ performance. The study also revealed that collaborative learning was significantly related to principals’ performance in public secondary schools in Delta State. The recommendations made included school principals exploring social media as a veritable avenue for connecting and learning in different experts in different social media tools and online academic community. The study also recommended that principals should maximize the benefits of teamwork, collaboration, and knowledge synergy with their professional colleagues as a pathway to improving their school leadership skills and competencies.